2014
DOI: 10.1063/1.4867494
|View full text |Cite
|
Sign up to set email alerts
|

Transient crystalline superlattice generated by a photoacoustic transducer

Abstract: Designing an efficient and simple method for modulating the intensity of x-ray radiation on a picosecond time-scale has the potential to produce ultrafast pulses of hard x-rays. In this work, we generate a tunable transient superlattice, in an otherwise perfect crystal, by photoexciting a metal film on a crystalline substrate. The resulting transient strain has amplitudes approaching 1%, wavevectors greater than 0.002 Å−1, and lifetimes approaching 1 ns. This method has the potential to generate isolated picos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…It has also been shown that when the acoustic phonon spectrum is modulated, these sidebands can be enhanced or cancelled 15 . Loether et al proposed a method for switching X-rays based on modulating the acoustic phonon spectrum in a semiconductor by using an optoacoustic transducer 16 . In that study, the X-ray reflectivity from photo-acoustic transducers was studied using a temporal resolution of 50 ps.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that when the acoustic phonon spectrum is modulated, these sidebands can be enhanced or cancelled 15 . Loether et al proposed a method for switching X-rays based on modulating the acoustic phonon spectrum in a semiconductor by using an optoacoustic transducer 16 . In that study, the X-ray reflectivity from photo-acoustic transducers was studied using a temporal resolution of 50 ps.…”
Section: Introductionmentioning
confidence: 99%
“…On the time scale of relevance here, only longitudinal expansion takes place, and the strain (σ) can be inferred from the mass density: σ(z, t) = ρ Al,s /ρ Al (z, t) − 1, where ρ Al,s is the density of solid Al, i.e., before the laser pulse. The strain profile in Al at a depth of 300 nm was extracted and an acoustic transmission coefficient from Al to InSb was applied based on the acoustic impedances of the two materials [22,23]. To reproduce the experimental laser conditions, simulations were performed using a range of absorbed fluences in Al similar to the experimental conditions.…”
mentioning
confidence: 99%